2014
DOI: 10.1111/bre.12045
|View full text |Cite
|
Sign up to set email alerts
|

Non‐uniform hyper‐extension in advance of seafloor spreading on the vietnam continental margin and the SW South China Sea

Abstract: The SW South China Sea preserves a propagating oceanic spreading centre and associated continent-ocean transition (COT) that characterizes the continental margin offshore SE Vietnam. We investigated the nature of strain accommodation in the region immediately in front of the propagating rift using a combination of 1-and 2-D backstripping subsidence reconstructions, coupled with forward modelling based on the measured upper crustal extensional faulting applied to a flexural cantilever model. Major normal faulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…For these reasons we believe that some Type II margins will be shown to contain core complexes, like those in extended backarc regions, e.g. the Aegean Sea (Lister et al, 1984;Jolivet et al, 2010) and possibly in the South China Sea (Savva et al, 2013;Li et al, 2014).…”
Section: Characteristics Of the Type I And Type Ii Rifted Marginsmentioning
confidence: 99%
“…For these reasons we believe that some Type II margins will be shown to contain core complexes, like those in extended backarc regions, e.g. the Aegean Sea (Lister et al, 1984;Jolivet et al, 2010) and possibly in the South China Sea (Savva et al, 2013;Li et al, 2014).…”
Section: Characteristics Of the Type I And Type Ii Rifted Marginsmentioning
confidence: 99%
“…Wu et al (2005) considered the NE margin as the upper-plate in the simple-shear rifting model (Lister et al 1986), and suggested that the HVL originated from asthenospheric underplating. As analog and numerical models show (Huismans et al 2014), continental extension is in general depth-related and strongly depends on interstratified decoupling, which is also proven by detailed geophysical data of the SCS Li et al 2014b). To complicate matters, deep structures detected along several margins are also dependent on initial settings of rifting, such Figure 1.…”
Section: Introductionmentioning
confidence: 81%
“…Seismic and deep borehole data acquired along and near the fossil spreading axis in the NE, Central and SW sub-basins of East Vietnam Sea revealed basalt and pyroclastic deposits interbedded with early Miocene (>16 Ma) sediments (Li et al, 2014(Li et al, , 2015. However, the rate and extent of the synspreading volcanism were modest, corresponding to slower to intermediate spreading rate (20 km to 35 km/Myr); although the spreading rate sometimes reached 70-80 km/Myr (Li et al, 2014;IODP 349 Scientific report, 2014).…”
Section: Decompression Melting: Mantle Dynamics Versus Lithospheric Ementioning
confidence: 99%
“…Plots of MgO (wt.%) against major oxides of Phu Quy basalts; except for SiO 2 which shows two broadly negative correlation trends with MgO for early and later eruptive lavas, the other oxides such as K 2 O, TiO 2 and P 2 O 5 define higher and lower fields, respectively, for late (circle) and early (diamond) lavas. Plotted for comparison are synopening East Vietnam Sea (cross, after Li et al, 2014) showing even lower in MgO, TiO 2 and K 2 O than Phu Quy basalts…”
Section: Major Element Compositionsmentioning
confidence: 99%
See 1 more Smart Citation